If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=160+-96H+-16H^2
We move all terms to the left:
-(160+-96H+-16H^2)=0
We use the square of the difference formula
-(160-96H-16H^2)=0
We get rid of parentheses
16H^2+96H-160=0
a = 16; b = 96; c = -160;
Δ = b2-4ac
Δ = 962-4·16·(-160)
Δ = 19456
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$H_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$H_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{19456}=\sqrt{1024*19}=\sqrt{1024}*\sqrt{19}=32\sqrt{19}$$H_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(96)-32\sqrt{19}}{2*16}=\frac{-96-32\sqrt{19}}{32} $$H_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(96)+32\sqrt{19}}{2*16}=\frac{-96+32\sqrt{19}}{32} $
| 3x+21=-6 | | S=7/8r+21 | | S=7/8r+147 | | 49=4v+17 | | 9x-15=-4x+15 | | 2x-5=-9x-6 | | 8(5x-4)=48 | | x^2-71x+540=0 | | 4/5(4x-7)=20 | | R=8/7s+21 | | 9^x+6.3^x=27 | | 3x-5(x+4)=-7x | | 3x+27=11x+53 | | 16x-36=7x-8 | | 5(2+x)=11 | | 6(7-4x)+7(2-5x)=45 | | 10x2-7x-5=0 | | -5m+8=33 | | 5505=2x+2000 | | -30=-2+7x | | 15x−14x−x+4x=4 | | -6m+8=-46 | | 3(0)+2y=3 | | -6p-4(4-3p)=3(p-4)-19 | | 25.8=1/4x | | 7x/2+5=3x/5-4 | | 3c÷9=4-c | | X^2+22x-5040=0 | | X+1/4x=4.5 | | 4(2x+13|)=80 | | 42=15u-9u | | 5x²-2x-3=0 |